PERAN SISTEM INFORMASI MANAJEMEN DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH - Sutrisnaniati, Eli; Azainil, Azainil; Junainah, Junainah; Widiayati, Widiayati (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the role of Management Information Systems (MIS) in improving the quality of education. The research method employed is a literature review with a qualitative analysis approach. The data collected includes scholarly articles, books, and research reports related to MIS and educational quality. The findings indicate that MIS implementation has been effectively executed in various educational institutions. The use of data management applications such as Dapodik and information technology within MIS supports the learning process, enhances efficiency and effectiveness in educational data collection, and facilitates teaching practices utilizing technological infrastructure. The analysis revealed that a universal information system model enables objective evaluation results, allows for the adjustment of evaluation criteria parameters and complexity, and determines the value and importance of parameters. Moreover, the implementation of integrated management information systems assists in decision-making to improve school quality and educational services. The conclusion of this research shows that MIS plays a crucial role in enhancing educational quality through effective data management, facilitating teaching practices, and increasing efficiency in data collection and processing. Thus, MIS can be considered a key strategy for improving overall educational quality